2000
DOI: 10.1073/pnas.050583597
|View full text |Cite|
|
Sign up to set email alerts
|

Posttranscriptional regulation of Bruton's tyrosine kinase expression in antigen receptor-stimulated splenic B cells

Abstract: Mutation of Bruton's tyrosine kinase (Btk) causes human X-linked agammaglobulinemia and murine X-linked immunodeficiency syndrome (xid). Quantitative aspects of B lymphocyte development and function have been demonstrated to depend on Btk level in vivo by using a murine transgenic model system. A sensitive intracellular immunofluorescent assay was developed to measure Btk protein on a per cell basis to test the hypothesis that its dosage is dynamically regulated during B cell dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 58 publications
(59 reference statements)
2
30
1
1
Order By: Relevance
“…Moreover, the total concentration of Btk does not change under the same conditions, and remains unchanged in cells pretreated with LPS and stimulated with the complexes. This finding is in contrast to those in studies showing an increase in the Btk expression of B cells (53,54).…”
Section: Discussioncontrasting
confidence: 56%
“…Moreover, the total concentration of Btk does not change under the same conditions, and remains unchanged in cells pretreated with LPS and stimulated with the complexes. This finding is in contrast to those in studies showing an increase in the Btk expression of B cells (53,54).…”
Section: Discussioncontrasting
confidence: 56%
“…In chicken DT40 B cells, Btk bound Fas directly, interfering with signaling for cell death, such that Btk-deficient DT40 cells were much more sensitive to Fas killing than wild-type (WT) control cells. Combined with the observation that Btk protein expression was up-regulated following sIg engagement (43), these results raise the possibility that Btk may be responsible for sIg-induced Fas resistance, either as a signaling intermediary, or as a terminal inhibitor of the Fas death pathway. The present study was conducted to examine the role of Btk in promoting sIg-induced Fas resistance, and the capacity of Btk to modulate the sensitivity of B cells to Fas killing.…”
mentioning
confidence: 74%
“…Intracellular levels of Btk may play an important role in a quantitative increase in BCR signaling with B cell maturation. Nisitani et al showed that Btk protein levels in splenic B cells are maximally increased (7-to 10-fold) within 4 h of BCR stimulation by a posttranscriptional mechanism involving Btk and PI3K (39). This up-regulation also occurs in vivo after T cell-dependent or T cell-independent immunization.…”
Section: Btk and Nf-b Positive Autoregulatory Loop Downstream Of Bcrmentioning
confidence: 96%